Lubang Resapan Biopori Jumbo Sebagai Teknologi Tepat Guna Untuk Pengolahan Sampah Organik - Kemuning Radhita Cahyani; Dwi Wahyuni, Nurul; Elfrida Laras Candrakusuma; Fadilla Ryandini; Praja Firdaus Nuryananda (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Biopore Infiltration Holes or LRBs are formed by the movement of plant roots, worms, termites and other soil organisms that live in the soil. This hole will later become the passage of air in the ground. The purpose of biopori is to restore soil fertility, protect water bodies, and preserve the environment. So that it can reduce the risk of flooding in areas with less air absorption. Biopori can be used as an appropriate technology that is simple and based on natural resources. Kedung Baruk Group 82 Thematic KKN utilizes biopori as TTG (Appropriate Technology). The method used in the process of making and maintaining LRB is by socializing and disempowering practitioners and the public through increased participation. The goal is to build public awareness about the importance of environmental sustainability in line with community sustainable development goals (SDG’s). Keywords: Biopori, SDGs, Appropriate technology